Teaching Strategies in Literature Subjects in Pup Taguig Branch Towards the Development of Instructional Modalities - Gordonas, A A (KnE Social Sciences, 2018)
The study focused on the teaching strategies in literature subjects towards the development of instructional modalities. The researcher made use of the descriptivesurvey method of research. Respondents of this study were 82 BSED English major students of Polytechnic University of the Philippines Taguig Branch. Based on the data analysed and interpreted, the following findings were deduced: In terms of their profile, majority of the respondents are aged 18-20 years old, female and single. As to direct instruction, lecture method dominated the teaching strategies. Meanwhile, from among the list of teaching strategies, the least used is the reinforcement of tape recordings. As to indirect instruction, discovery method ranked number 1 and lowest in rank is case study. As to Interactive Instruction, recitation got the highest rank while debate was revealed having the lowest mean verbally interpreted as Occasionally. As to individual study, reports ranks number 1 while distance education got the lowest mean. As to experiential instruction, dramatization got the highest mean. Meanwhile, case studies had the lowest mean. Interactive teaching dominated among the teaching strategies used by literature teachers verbally interpreted as Frequently while the least is direct instruction. There is no significant difference in the assessment of the respondents on the teaching strategies in literature subjects in terms of age. However, their perceived assessment on direct instruction, indirect instruction, individual study entails that there is a significant difference on the teaching strategies in literature subjects when grouped by the age of the respondents. There is no significant difference on the teaching strategies in literature subjects when grouped by gender of the respondents on the teaching strategies in literature subjects. However, there exists a significant difference on the experiential learning among male and female students. There is no significant difference in the assessment of the respondents on the teaching strategies in literature subjects in terms of civil status. Keywords: Teaching Strategies, Literature, Direct Instruction, Experiential Strategy, Interactive Teaching Strategy